Tutoplast bioimplants as an alternative to autobone in treating hand enchondromata - Baliy, Sergey; Daragan, Ruslan; Tovstogray, Vadym (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The authors share their experience of treating 23 patients with enchondromata of the finger phalanges with use of different plastic materials for replacing defects of the phalanges after the removal of enchondromata. Preference is given to Tutoplast.